Gas Discharge Plasmas and Their Applications (GDP 2019): 14th International Conference, September 15–21, 2019, Tomsk, Russia; abstracts - Korolev Yu. D. Yuriy Dmitrievich; Koval N. N. Nikolay Nikolaevich (Tomsk, TPU Publishing House, 2019)
Title screen